Akulturasi Islam Dan Adat Dalam Seloko Jambi: Warisan Lisan Penuh Nilai - Desfianti, Safina; Hudaidah, Hudaidah (LPPM Politeknik Pratama, 2025)
This article discusses the acculturation process between Islam and adat in the oral tradition of seloko that developed among the Jambi Malay community. Seloko, as a customary expression passed down from generation to generation, not only contains cultural values, but also becomes a medium for internalizing Islamic teachings in a contextual and local form. Through a descriptive qualitative approach and literature study, this article shows that Islamic values such as justice, deliberation, obedience to God, and respect for others are deeply embedded in the philosophical and practical structure of seloko. The process of Islamization in Jambi took place peacefully and harmoniously through a cultural approach, where ulama and traditional leaders made seloko a means of da'wah and character education. The integration of customary law and Islamic law is also reflected in the use of seloko in traditional deliberation forums that unite social, religious and legal aspects.